(untitled) (Journal of Medicine, 2025)
Introduction: Although similar in the initial presentation, monomelic amyotrophy (MMA) and amyotrophic lateral sclerosis (ALS) have different courses, management protocols, and outcomes. Correct diagnosis of MMA and ALS is crucial in the management aspect. This study aimed to assess the utility of nerve conduction study (NCS) to differentiate MMA from ALS and also to develop an NCS-based scoring system for this purpose. Methods: This diagnostic accuracy study included 17 patients with MMA and 37 patients with ALS. Motor NCS parameters of the median and ulnar nerves were compared between the two groups. An NCS-based scoring system, ‘HANS’, was developed from the parameters with significant differences between the two groups, and its diagnostic validity to differentiate MMA from ALS was assessed. Results: Both MMA and ALS showed a male predominance. The median age was lower in MMA, 24(18-34) years than in ALS, 37(25-55) years. HANS (Hirayama AIS res score) showed 77% sensitivity and 78% specificity, with a good overall diagnostic accuracy of 78%. Conclusion: The use of HANS may facilitate the differentiation of MMA from ALS and aid in directing appropriate treatment. Key words: Monomelic amyotrophy, amyotrophic lateral sclerosis, nerve conduction study, HANS. J MEDICINE 2025; 26(2): 94-100